Jogo do perito: aprendizagem baseada em jogos para aprendizagem de cinemática - Leão, Jackson Vieira Barbosa (2022)
Data from IPEA indicate that Brazil is among the top 5 countries with the highest number of traffic victims. Based on this information and motivated by a report on forensic analysis, a didactic proposal was created in order to raise awareness and foster the learning of kinematic concepts for first grade high school students. The proposal was to investigate a fictitious accident involving two vehicles at an intersection of streets in downtown Aracaju/SE. The students should assume the role of criminal experts to evaluate the evidence they receive and, based on their conclusions, judge those responsible for the collision. The game-based learning (GBL) was used as a methodological strategy to implement the product. Students access the evidence through the Genially website, (the virtual environment where the Forensic Game was developed) and as they advance in the product's research they receive immediate feedback, relying on tools of a game, where they are constantly challenged and provide interaction with peers and disputes. The stages of investigation then follow the pattern of a game where the difficulties are increasing and as the game progresses, the students are exposed to a real strategy used by experts to solve problems involving traffic accidents. The frame check and analysis of traffic laws.